Egypt 2026 - Tabbaa, Sanad; Buxbaum, Jessica; Fitzpatrick, Mary, 1962-; Hardy, Paula, 1973-; Jackson, Anthon; Keith, Lauren; Obeid, Lama; El Sawy, Nada; Galal, Shoroq (Lonely Planet guidebooks., 2025)
This comprehensive guide extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Discover the pyramids of Giza, cruise the Nile, and dive in the Red Sea; all with your trusted travel companion.